Natura juridică a sancțiunilor prevăzute de legislația referitoare la integritate - Reniță, Gheorghe (CEP USM, 2024)
Legislation related to integrity provides for several sanctions likely to be applied to a public agent in the case that he holds unjustified wealth. Namely, it is about: 1) release from the position held or termination of the mandate; 2) prohibition to exercise a public office and/or a position of public dignity for a period of three years; 3) confiscation of unjustified wealth. At the same time, the Criminal Code provides for liability for illicit enrichment. Under these conditions, the question of the parallelism between the non-criminal procedure and the criminal procedure was raised. In order to elucidate this aspect, it is indispensable, first of all, to clarify the legal nature of the sanctions provided by the integrity legislation. In this sense, the starting point is the Engel test.
LEGAL NATURE OF SANCTIONS PROVIDED BY INTEGRITY LEGISLATION
Keywords: unjustified wealth; substantial difference; public agent; integrity; sanctions